Keselamatan Dalam Pandangan Calvinisme dan Implikasinya Bagi Jemaat - Karauwan, Gabriel Theovani (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2023)
This thesis discusses how salvation in the view of Calvinism is implied for the GMIM Moria Wulurmaatus congregation. The dogmatic problem found is the phenomenon of an understanding of salvation that is not in accordance with the view of Calvinism, there are also factors that influence the congregation's view of salvation, the understanding of salvation has not been followed in daily life practices by members of the congregation in accordance with the view of Calvinism. Therefore, researchers will examine this soteriological issue from a Calvinist perspective. In this thesis, the researcher will use qualitative methods to dogmatically examine salvation in the view of Calvinism and its implications for the GMIM Moria Wulurmaatus Congregation, Modoinding Region. The researcher argues that Calvinist theology is a biblical theology that answers the congregation's need for an understanding of salvation in the midst of challenges that are relevant to the current situation.